Physical development of pre-school children rom the prospective territory of “Katowice” steel mills influence - Kmiecik-Rajtko, Helena; Gralla, Gertruda; Konecki, Janusz (Anthropological Review, 1980)
The authors have conducted anthropometrical examinations of 290 children of age 4-7 years from areas expected to fall within scope of influences of the newly build “Katowice” steel mills. Results of these examinations were compared with those obtained for children of the same age from other urban and rural regions of Silesia. It has been found that children examined in the present study have the lowest values of compared characteristics. The authors hope that this fact will undergo change in response to complex influences exerted by close neighbourhood with large, new steel mills.